2020
DOI: 10.3390/info11030160
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Results of a Data Envelopment Analysis Model and Logit Model in Assessing Business Financial Health

Abstract: This paper focuses on business financial health evaluation with the use of selected mathematical and statistical methods. The issue of financial health assessment and prediction of business failure is a widely discussed topic across various industries in Slovakia and abroad. The aim of this paper was to formulate a data envelopment analysis (DEA) model and to verify the estimation accuracy of this model in comparison with the logit model. The research was carried out on a sample of companies operating in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…513/1991 Coll. Commercial Code [49] of the Slovak Republic; therefore, it occurs mainly in Slovak studies, e.g., [78][79][80][81][82][83][84].…”
Section: Discussionmentioning
confidence: 99%
“…513/1991 Coll. Commercial Code [49] of the Slovak Republic; therefore, it occurs mainly in Slovak studies, e.g., [78][79][80][81][82][83][84].…”
Section: Discussionmentioning
confidence: 99%
“…Shetty et al (2012) applied the DEA model to determine the assumption of bankruptcy of the analyzed sample of businesses. The result of their study was the proposal of indicators that should be applied as predictors of bankruptcy (in Horváthová and Mokrišová 2020). It is also possible to mention the research of Ouenniche and Tone (2017), who proposed an out-of-sample evaluation framework for DEA and confirmed that DEA as a classifier is a very suitable contender for discriminant analysis.…”
Section: Introductionmentioning
confidence: 98%